Code Reviews Do Not Find Bugs. How the Current Code Review Best Practice Slows Us Down - Czerwonka, Jacek; Greiler, Michaela (IEEE - Institute of Electrical and Electronics Engineers, 2015)
Because of its many uses and benefits, code reviews are a standard part of the modern software engineering workflow. Since they require involvement of people, code reviewing is often the longest part of the code integration activities. Using experience gained at Microsoft and with support of data, we posit (1) that code reviews often do not find functionality issues that should block a code submission; (2) that effective code reviews should be performed by people with specific set of skills; and (3) that the social aspect of code reviews cannot be ignored. We find that we need to be more sophisticated with our guidelines for the code review workflow. We show how our findings from code reviewing practice influence our code review tools at Microsoft. Finally, we assert that, due to its costs, code reviewing practice is a topic deserving to be better understood, systematized and applied to software engineering workflow with more precision than the best practice currently prescribes.